ANALISIS HUKUM KONFLIK PERTANAHAN DI PEDESAAN: (Studi Kasus Sengketa Lahan Antara Masyarakat Desa Talonang Dengan Pemerintah Kabupaten Sumbawa Barat) - Lili Abdullah (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2021)
The land conflicts that have occurred in talonang village, Sekongkang sub-district, West Sumbawa regency originated from the victims of the 1977 Tjunami.On October 17, 1992, the Governor of West Nusa Tenggara issued Decree No. Ropang District and Jereweh District. In 2012, the Ministry of Manpower and Transmigration of the Republic of Indonesia once encouraged investment in the reserve area. Among them is working with the company PT. Dongfang Sisal Group itd, then Gandng China developed and it is the material used to make ropes and make it a superior product. Finally, the West Sumbawa Regency Government gave a permit to PT. Sumbawa Agro Island for sisal cultivation. This incident raises a question about the status of the land which is the object of the dispute between PT. Sumbawa Agro Island with the Talonang Indigenous Peoples and how the District Government's policies in resolving disputes between PT. Sumbawa Agro Island with the Talonang Indigenous Peoples of the District. West Sumbawa ?. The method used is juridical empirical with an approach to cases, facts and history to find out the existing problems. The settlement process was carried out by means of mediation by the West Sumbawa Regency Government.